Utopia as “No-Place”: Utopias, Colonialism and International Law - Ruth Houghton; Aoife O'Donoghue (Law Text Culture, 2023)
Utopia, etymologically, is both the no-place (ou-topos) and the good-place (eu-topos). For Thomas More, his no-place was a ‘New Island’, an imaginary location in the “New World”. Yet, More’s no-place is inhabited. More’s utopian construction begins with the displacement of indigenous communities. From the 17th to 19th century, across much of Western utopian literature, no-places were constructed through colonial exploits. Through ideas of “discovery” alongside the displacement of indigenous communities, regulating women’s bodies (the literal putting of people in their place), the invocation of science and ideas of civilisation, colonial utopias were created. Strikingly, these narratives bare unmistakable similarities with the colonial discourses of international law. International law supplied the basis for creating no-place. It made fine distinctions based on “proper” land use that led to mass violence against indigenous populations. Intersecting with scholarship that traces the role of utopian literature in colonialism, this article explores how white western patriarchal utopian projects – the “canonical” utopian texts - influenced and were influenced by international law. This paper assembles a taxonomy of no-place within Western utopian literature, using feminist and post-colonial utopian critiques to problematise the construing of Terra Incognita Australis as no-place. Reading utopian literature from feminist and post-colonial perspectives highlights tensions around the idea of no-place and offers a basis to begin imagining a decolonised law. For there is no “no-place”, just as the lands (and seas) in the fictional utopias were (generally) inhabited, colonised lands are indigenous people’s places, their homes, their communities, and their lives.